A role for curcumin in preventing liver fibrosis in animals: a systematic review and meta-analysis - Huang, Bo-Hao; Guo, Zi-Wei; Lv, Bo-Han; Zhao, Xin; Li, Yan-Bo; Lv, Wen-Liang (Frontiers in Pharmacology, 2024)
Objective: This meta-analysis aimed to determine the efficacy of curcumin in preventing liver fibrosis in animal models.A systematic search was conducted on studies published from establishment to November 2023 in PubMed, Web of Science, Embase, Cochrane Library, and other databases. The methodological quality was assessed using Sycle's RoB tool. An analysis of sensitivity and subgroups were performed when high heterogeneity was observed. A funnel plot was used to assess publication bias.: This meta-analysis included 24 studies involving 440 animals with methodological quality scores ranging from 4 to 6. The results demonstrated that curcumin treatment significantly improved Aspartate aminotransferase (AST)[ standard mean difference (SMD) =-3.90, 95% confidence interval (CI) (-4.96, -2.83), p＜0.01, I 2 = 85.9%], Alanine aminotransferase(ALT)[ SMD=-4.40, 95% CI (-5.40, -3.40), p＜ 0.01, I 2 = 81.2%]. Sensitivity analysis of AST and ALT confirmed the stability and reliability of the results obtained. However, the funnel plot exhibited asymmetry.Subgroup analysis based on species and animal models revealed statistically significant differences among subgroups. Furthermore, curcumin therapy improved fibrosis degree, oxidative stress level, inflammation level, and liver synthesis function in animal models of liver fibrosis.Curcumin intervention not only mitigates liver fibrosis but also enhances liver function, while concurrently modulating inflammatory responses and antioxidant capacity in animal models. This result provided a strong basis for further large-scale animal studies as well as clinical trials in humans in the future.